1982
DOI: 10.1016/0031-9384(82)90331-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term isolation increases social interactions of male rats: A parametric analysis

Abstract: NIESINK, R. J. M. AND J. M. VAN REE. Short-term isolation increases social interactions of male rats: A parametricanalysis. PHYSIOL. BEHAV. 29(5) [819][820][821][822][823][824][825] 1982.--Frequencies of social interactions were higher in pairs of short-term individually housed male Wistar rats as compared to group-housed animals. This was most pronounced when an individually housed rat and a group-housed conspecitic were tested together in the morning under red light conditions. Then, in particular the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 29 publications
(31 reference statements)
10
86
0
Order By: Relevance
“…Extinction of active avoidance behavior appeared to be facilitated in phase-shifted rats as compared to controls, indicating that the amnesia induced by phase-shifting is not restricted to passive avoidance behavior. Previous studies have shown that changes in the environment before (isolation for 4-7 days) or during (intense light) testing markedly affect the level of social behaviors of rats tested in dyadic encounters [7,8]. However, neither reversal of the illumination cycle nor continuous exposure to light changed the various aspects of social interactions and explorative behavior.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Extinction of active avoidance behavior appeared to be facilitated in phase-shifted rats as compared to controls, indicating that the amnesia induced by phase-shifting is not restricted to passive avoidance behavior. Previous studies have shown that changes in the environment before (isolation for 4-7 days) or during (intense light) testing markedly affect the level of social behaviors of rats tested in dyadic encounters [7,8]. However, neither reversal of the illumination cycle nor continuous exposure to light changed the various aspects of social interactions and explorative behavior.…”
Section: Discussionmentioning
confidence: 95%
“…Testing was performed by placing two rats (an experimental rat and a rat exposed to the normal light/dark cycle) together in a perspex observation cage illuminated with red lights for 10 minutes [7,8]. The behavior of rats was analysed later from video tapes by individuals who did not know the illumination schedule of the rats.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with the expectations, based on t~te report by Wade and Mater, that impoverishment for 2-3 weeks impaired Morris maze performance of rats without a lesion, and these deficits grew more severe as the period of impoverishment increased [28]. After long-term impoverished housing rats develop an array of behavioural changes, including, amongst others, increased aggression [ 14,26], high locomotor activity [112] and altered social behaviour [ 17]. Several authors have contributed the impoverishment effect to a 'hyperreactivity to environmental stimuli' or 'hyperarousal' [6,10,14].…”
Section: Discussionmentioning
confidence: 63%
“…Einon has shown that IC effects on object contact and radial arm maze learning could not be induced when rats were first introduced to the impoverished condition after 45/50 days of age [5,6], but emergence from cover in an open field could be affected by impoverishment at any time [6]. Some behaviours seem to be susceptible to impoverishment starting well after weaning; rats impoverished at young adult age are slower to extinguish conditioned taste aversion [13], and upon resocialization after a period of impoverishment rats show an increase in social grooming and approach the other animal more [17]. When impoverishment lasts for weeks or even months several behavioural differences can be distinguished: rats become more aggressive [18], explore more in a holeboard task [7] and are hyperactive when introduced into a novel environment [ 11].…”
Section: Introductionmentioning
confidence: 99%